PENGARUH CITRA DESTINASI TERHADAP KEPUASAN WISATAWAN DAN BEHAVIORAL INTENTION - R.M, Cory Caroline (FIA UB, 2021)
This study aims to examine the effect of the destination image variable on tourist satisfaction when visiting and its impact on behavioral intention. This research was conducted at the Nusa Penida tourist destination, Bali, Indonesia. This type of research is an explanatory research with a quantitative approach. The research data was taken directly using a questionnaire to 310 respondents with purposive sampling technique and then analyzed using the PLS model. The results showed that the image of the destination had a positive and significant influence on tourist satisfaction and behavioral intention. Tourist satisfaction also has a positive and significant effect on behavioral intention. The findings of this study strengthen the results of previous research and are in line with the grand theory of S-O-R